2018
DOI: 10.1002/mats.201800029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Micrometer‐Size Poly(Methyl Methacrylate) Particles by Utilizing Microsuspension Iodine Transfer Polymerization (ms ITP): Kinetic Approach

Abstract: In a previous work, microsuspension ITP (ms ITP) of methyl methacrylate (MMA) using iodoform (CHI3) as a chain transfer agent and benzoyl peroxide (BPO) as an initiator could be successfully carried out at 80 °C for the synthesis of micrometer‐size poly(MMA) (PMMA) particles without the byproduct of submicrometer‐size particles. Whereas, in microsuspension conventional radical polymerization (ms CRP) at the same conditions except for non‐use of CHI3, about half amount of PMMA was formed as submicrometer‐size b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It was reported that high R p w plays an important role in homogenous nucleation. 36 More specifically, from the view of the solubility of oligomers, the maximum monomer units of an oligomer radical (P max ) at 80 °C, which can still exit from monomer droplets is 4 for the PMMA oligomer, while that of the PMA oligomer is 26, which were calculated using eq 7 in the Supporting Information. This higher water solubility of the PMA oligomer caused the difficulty in the formation of microsuspension of MA.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that high R p w plays an important role in homogenous nucleation. 36 More specifically, from the view of the solubility of oligomers, the maximum monomer units of an oligomer radical (P max ) at 80 °C, which can still exit from monomer droplets is 4 for the PMMA oligomer, while that of the PMA oligomer is 26, which were calculated using eq 7 in the Supporting Information. This higher water solubility of the PMA oligomer caused the difficulty in the formation of microsuspension of MA.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Simulations for ITP and CRP of MA were conducted with PREDICI software from CiT GmbH (Rasfede, Germany) using the kinetic parameters shown in Table S1, in the same way as reported in the previous article. , The kinetic model was built based on the assumption of the fate of free radicals (Scheme S1) and was explained in detail in the simulation section in the Supporting Information. The simulation was composed of individual reaction steps: initiation, propagation, termination, and chain-transfer reactions and their kinetic coefficients.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…† Simulation of the ITP of VAc was conducted using the PREDICI software from CiT GmbH (Rasfede, Germany) with the kinetic scheme and parameters shown in Tables S2 and S3, † as previously reported. 29,32 The kinetic model is explained in the simulation section of the ESI. † The simulation comprised the following individual reaction steps: initiation, propagation, termination, and chain transfer reactions, including their kinetic coefficients.…”
Section: Model and Governing Equations Used For The Polymerization Mechanismmentioning
confidence: 99%
“…Meanwhile, only a few reports have described the use of ITP to prepare PVAc, 8,25,26 mainly focusing on homogenous systems, with only one example reported by Lacroix-Desmazes et al using a miniemulsion system. 8 When employing a hydrophilic monomer in a suspension or microsuspension system, the initiator or oligomeric radicals generated in the monomer droplets can easily exit from the droplets to the aqueous medium, resulting in the formation of submic-rometer-sized byproduct particles through emulsion polymerization, [27][28][29][30] which hinders the control of the molecular weight and molecular weight distribution in RDRP. Therefore, the synthesis of micrometer-sized particles through microsuspension polymerization of VAc (solubility in water: 2.3 g per 100 mL at 20 °C) without obtaining submicrometersized particles as a byproduct is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The latter aim is usually regarded as the difficulty of hydrophilic monomers in a conventional suspension or microsuspension system, which is accompanied by submicrometer-sized particles since the homogenous nucleation in the aqueous phase is difficult to be restrained. [13][14][15][16] The success of the ms ITP of hydrophilic monomers relies on the radical exit depression effect, according to which the escaping monomer and oligomer radicals can be captured by the highly hydrophobic diiodomethyl group and iodine group from CHI 3 in the monomer droplet. 17,18 The ms ITP of methyl methacrylate (MMA) (solubility in water: 1.5 g per 100 mL, at 20 °C) 19 resulted in micrometer-sized particles.…”
Section: Introductionmentioning
confidence: 99%